Adaptabilitas dan Relevansi Kompetensi Lulusan Perguruan Tinggi dalam Karier Nonlinier: Studi Kasus Individu - Nuri Safitri (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the adaptability and relevance of competencies among university graduates in navigating non-linear career paths. This research employs a qualitative approach using a case study method involving a Public Administration graduate working at the Nutritional Fulfillment Service Unit (SPPG). Data were collected through in-depth interviews. The findings show that although the career path is not fully aligned with the initial plan, competencies acquired during higher education remain relevant, particularly in administrative tasks and public service. In addition, adaptability, accuracy, and responsibility are key factors supporting individual performance. This study concludes that non-linear careers represent a form of adjustment to the dynamic labor market rather than merely a deviation from educational background.